PEMANFAATAN TEKNOLOGI WEB SERVICE UNTUK INTEGRASI SISTEM LAYANAN MATERI PELAJARAN TERDISTRIBUSI - Astika AyuningTyas; Ahmad Ashari (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2016)
The program is implemented by the National Agency of Standardization Education (BSNP) in principle requires the student's participation in the information of various media, one of which comes from the Internet. The role of the school, especially teachers by providing a source material is also very necessary. The more resources available subject should be one of the student's notes of support factors. Digital training network creative services can be an effective learning tool. Digital materials services can be used to connect between the school as a hardware provider, so that information systems can be integrated with each other learning materials between schools and many resource materials obtained . While the data can be integrated materials between schools then use the Web service. Web services are built on a system of service providers that are in each school. The results of the use of Web services technology for systems integration services which are the subject of each school, with testing services that are built at the school system testing and information important that is accessible by the user, ie teachers, students, and office. The results of the study indicate a web service to solve problems by providing a lot of information distributed on the providers and users as needed.